PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA SDM DI ORGANISASI PERANGKAT DAERAH (OPD) KOTA SUKABUMI - Siska Ayudia Adiyanti (Jurnal Manajemen Bisnis Performa, 2016)
This study aims to obtain empirical evidence about the "Influence of Transformational Leadership and Organizational Culture on the Performance of Human Resources in the regional organization device (OPD) of Sukabumi". The results are expected to contribute in the development of management science, especially human resource management, and more specifically about transformational leadership, organizational culture, and performance of human resources. This research is expected to provide input to the regional organization device (OPD) of Sukabumi in general, the knowledge and input in optimizing the performance of the institution.